Exploring Stockholm Syndrome in Belle's Character in Beauty and the Beast (2017): A Psychological Analysis Using Attachment and Trauma Bonding Theories - Retno Dwigustini; Vini Febriza (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study investigates the relationship between Belle and the Beast in Beauty and the Beast (2017), often discussed in psychological literature in terms of Stockholm Syndrome. Utilizing John Bowlby’s Attachment Theory and Patrick Carnes' Trauma Bonding Theory, this research analyzes the emotional dynamics between Belle and the Beast to assess whether their bond reflects psychological trauma or genuine love. The analysis focuses on key scenes that depict emotional dependence, power imbalance, and fluctuating affection, revealing a complex relationship that blends elements of trauma bonding and healthy attachment. This paper suggests that while the relationship demonstrates characteristics of Stockholm Syndrome, it also reflects mutual emotional growth and trust, ultimately contributing to a broader understanding of psychological attachment in popular media. The study provides new insights into how these dynamics are represented in film, offering a nuanced view of relationships marked by power imbalance and emotional transformation.